PENGARUH DAKWAH DI INSTAGRAM TERHADAP PERILAKU KEAGAMAAN MAHASISWA - Nurdin Nurdin; Muhammad Ridwan; Fitriningsih Fitriningsih (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2020)
This research is motivated by the rapid development of technology and information, one of which is social media, one of the most popular social media is Instagram. Instagram is a social media with a photo and video processing system and more practical information acquisition, the advantages that are presented by Instagram social media are able to reach the most users of other social media including students. The content in Instagram is not just information and entertainment, Instagram also offers news about Islam that can affect users, including students. The problems in this research are: finding out the influence of da'wah on Instagram on the religious behavior of university students. The question of this study is whether preaching on Instagram influences the religious behavior of university students. The purpose of this study was to determine whether preaching on Instagram influences the religious behavior of university students. This research is a quantitative study, with data collection methods through survey. The data analysis method used is the normality test, hypothesis testing and simple linear regression coefficient test which is then processing the data using the SPSS 16 for windows application. The population in this study was all students of communication and broadcasting Islam department from the year 2015 to the year 2018. The sampling technique used was purposive sampling technique, as many as 60 people by determining active users on Instagram. The results of processed statistics are assisted with SPSS 16 for window program, which shows that preaching on Instagram (X) significantly influences the religious behavior (Y) of Islamic broadcasting communication students with a sig value smaller than the value (α) of 0,000 <0.05 with the magnitude of its influence is 0.526 or 52.6%, while the remaining 47.6% is explained by other independent variables not included in this study.